LITERATURE REVIEW: EFEKTIVITAS MODEL PROJECT BASED LEARNING BERBANTUAN FLASHCARD BERBASIS AUGMENTED REALITY DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR - Rullyta Jani Irawati; Sri Sumartiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The rapid advancement of educational technology in the 21st century has reshaped the paradigm of science learning in elementary schools, emphasizing the need for students to develop critical thinking, collaboration, and creativity. This literature review investigates the effectiveness of integrating the Project-Based Learning (PjBL) model with Augmented Reality (AR)-based Flashcards to enhance elementary students’ critical thinking skills in Integrated Science (IPAS) education. Employing a Systematic Literature Review (SLR) method, this study analyzed publications from 2015–2025 sourced from reputable databases such as Scopus, ERIC, ScienceDirect, and SINTA. The data were examined through content analysis to identify key pedagogical themes, effectiveness, and research gaps regarding the integration of PjBL and AR in primary-level instruction. Findings reveal that AR-assisted PjBL significantly improves students’ conceptual understanding, engagement, motivation, and higher-order thinking skills by merging hands-on learning with visual and interactive experiences. Nevertheless, few empirical studies have simultaneously explored both approaches in the IPAS context. The review concludes that PjBL assisted by AR Flashcards holds substantial potential to enhance critical thinking, creativity, and scientific literacy among primary learners. Future research is recommended to conduct longitudinal and experimental studies to validate its long-term pedagogical effectiveness and scalability across diverse educational contexts.